Influencer’s Role In Applyıng The Envıronmental Lıfestyle To Brand Trust And Purchase Intentıon - Agustina Fitrianingrum; Sinya Rita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The purpose of this study was to determine the effect of Parasocial Relationship, influencer credibility, Perceived Behavior, Brand Trust and Purchase Intention to environmentally friendly products. The variables contained in this study are the independent variables, namely Parasocial Relationship and Perceived Behavior, the dependent variable is Brand Trust and Purchase Intention and also the mediating variable, namely Influencer Credibility. In this study, the sample used was 250 with purposive sampling method through online distribution. SPSS software version 26.0 and SmartPLS version 3.0 were used in the analysis of research data. The results of this study indicate that Parasocial Relationship, influencer credibility, Perceived Behavior, Brand Trust and Purchase Intention show a significantly positive influence. Based on the results of this study, an explanation of the influence of influencers is greatly influenced in the application of an environmentally friendly lifestyle to increase the protection of the surrounding environment.